Optimizing user experience: designing an engaging educational mobile application for english vocabulary knowledge and, student engagement in higher education - Yang, Tiantian; Razali, Abu Bakar; Zulkifli, Nurul Nadwa (UK Zhende Publishing Group, 2023)
This study explores the potential of educational mobile applications (apps) in Chinese higher education for English as a Foreign Language (EFL) learning. Amidst increased mobile device usage among college students, educational apps offer promise for enhancing language learning. However, their true impact on student performance and the intricate relationship between app design, English vocabulary knowledge, and student engagement remain insufficiently explored. To bridge this gap, a comprehensive study involving 326 Yunnan Minzu University students was conducted. Utilizing partial least squares structural equation modeling (PLS-SEM), our analysis aimed to assess how engaging educational apps impact English vocabulary development and student engagement. Additionally, we examined the role of language skills and student involvement as potential moderators between app design and English academic achievement. Results indicate that well-designed educational apps significantly improve English vocabulary knowledge and increase student engagement. This underscores app design's pivotal role in enhancing academic success in English language learning. Moreover, language proficiency and student involvement were found to moderate the relationship between app design and English academic achievement, emphasizing personalized learning's potential to boost student motivation and overall success. Theoretical implications emphasize the critical role of app design in augmenting vocabulary acquisition and encouraging active student participation. This study provides insights into designing purposeful educational apps for effective EFL learning, benefiting educators and developers, and contributing to technology-enhanced language learning literature.